84.7k views
3 votes
What is the math work to this equation
-6(-5+2)=56?

User Winestone
by
6.0k points

2 Answers

4 votes

-6(-5+2)=56

First step; brackets.

-5+2 = -3

-6(-3)=56

-6 x -3 = 18, because a negative times a negative gives you a positive.

I'm not sure where the 56 came from? Or maybe I misunderstood the question? Either way, I hope I helped.

User RazvanParautiu
by
5.3k points
5 votes

Answer:

18 ≠ 56

Explanation:

-6(-5+2)=56

-6(-3)=56

-18=56

the statement is false

User Bells
by
5.5k points